The hydrolysis of ammonia borane catalyzed by NiCoP/OPC-300 nanocatalysts: high selectivity and efficiency, and mechanism. Issue 4 (5th February 2019) - Qu, Xiaopeng; Jiang, Rui; Li, Qian; Zeng, Fanan; Zheng, Xue; Xu, Zhimou; Chen, Cunhua; Peng, Jing
Abstract : The development of highly efficient and cheap catalysts for the release of hydrogen from chemical hydrogen-storage materials is indispensable for the coming clean energy economy. Abstract : The development of highly efficient and cheap catalysts for the release of hydrogen from chemical hydrogen-storage materials is indispensable for the coming clean energy economy. ZIF-67 is transferred into oxygen-doped porous carbon (OPC-300) using two-step heat treatment for the first time. The OPC-300 nanomaterial appears much more effective than other supports, including ZIF-67, graphene oxide and MOF-74, for Ni0.66 Co0.19 P0.15 nanoparticles. NiCoP/OPC-300 nanocatalysts, obtained for the first time, have been successfully synthesized via a facile one-step chemical reduction method. Owing to highly effective quadruple synergy between Ni, Co, P and OPC-300, the prepared noble-metal-free Ni0.66 Co0.19 P0.15 /OPC-300 nanocatalyst exhibits superior catalytic activity for hydrogen evolution from the hydrolysis of ammonia borane, with a TOF value of up to 95.24 molH2 molcat −1 min −1 in NaOH (0.4 M) solution at 298 K.